Comparison of Sebia Capillarys Capillary Electrophoresis With the Primus High-Pressure Liquid Chromatography in the Evaluation of Hemoglobinopathies - David F. Keren; Deborah Hedstrom; Ronald Gulbranson; Ching-Nan Ou; Richard Bak (2008)
The Sebia Capillarys (capillary zone electrophoresis [CE]) and the Primus Resolution high-pressure liquid chromatography (HPLC) were used to prospectively evaluate 297 samples for hemoglobinopathies. Hemoglobin (Hb) A levels were similar on both techniques (mean, 96.2% and SD, 5.7% by CE; mean, 96.8% and SD, 5.5% by HPLC), but HbA2 levels were higher by CE (mean, 2.8%; SD, 0.8%) than by HPLC (mean, 2.3%; SD, 0.8%). HbS had higher values by CE (mean, 40.6%; SD, 18.9%) than by HPLC (mean, 38.4%; SD, 18.9%). In cases with Hg S, HbA2 levels were greater by HPLC (mean, 4.0%; SD, 1.0%) than by CE (mean, 3.1%; SD, 0.8%). HbA2 was occasionally not separated sufficiently from HbC for measurement by CE, but did separate from HbE by CE. Both methods identified HbS, HbC, HbE, HbS, and HbC together, HbA2&prime, HbD-Los Angeles, HbF variant, HbG-Philadelphia, HbS-G Philadelphia, and Hb Lepore.